Sex, the picaresque and the glamorous revolution Nadine Gordimer's A Sport of Nature - Lazar, K. (My University, 1997)
Since South Africa's 1994 elections, a number of cultural works have come out which incorporate the build-up to social transformation as their subject matter. Nadine Gordimer's most recent novel to date, None to Accompany Me (1994), explores the politics of negotiation which led to South Africa's first democratic election as well as the optimisms and tensions of the years following Nelson Mandela's release from prison. In this most recent novel, Gordimer's commitment to the new social order as led by the African National Congress is both rearticulated and probed. The narrative deals with the daily work of politics and establishes a complex though localised focus on South Africa's recent moment. In the light of this recent novel by Gordimer, it is interesting to reread an earlier work by the author where a less bounded, more Utopian vision is present. A Sport of Nature (1987) offers a grand, energetic journey into an imagined African history as the backdrop against which South Africa's particular trajectory (past and future) may be read. This novel speaks of Gordimer's political imagination at its most unfettered, it spells out the wish that her subsequent novels put into more concrete and localised terms. My concern is to assess Gordimer's political project in A Sport of Nature in the light of the apparently "Utopian" versions of female sexuality and identity she here puts forward. Through the central figure of Hillela, especially, aspects of Gordimer's overall vision can be gauged. A Sport of Nature has provoked a high degree of interpretive divergency. Some critics have hailed it as Gordimer's "most optimistic" novel (Cooper 1990: 68) in the politics it offers, others as her "most deeply cynical" (Krauss 1 987: 33). Much critical focus has centred around the primary figure of Hillela, and again, opinion is strikingly divided: is Hillela an inspirational new type of political being, a feminist's nightmare, a modern female picaro, or all/none of these things?
African Studies Seminar series. Paper presented 3 March 1997
Keywords: Gordimer, Nadine,1923-; A Sport of Nature